2018
DOI: 10.1007/s00253-018-9154-7
|View full text |Cite
|
Sign up to set email alerts
|

Upregulating the mevalonate pathway and repressing sterol synthesis in Saccharomyces cerevisiae enhances the production of triterpenes

Abstract: Pentacyclic triterpenes are diverse plant secondary metabolites derived from the mevalonate (MVA) pathway. Many of these molecules are potentially valuable, particularly as pharmaceuticals, and research has focused on their production in simpler and more amenable heterologous systems such as the yeast Saccharomyces cerevisiae. We have developed a new heterologous platform for the production of pentacyclic triterpenes in S. cerevisiae based on a combinatorial engineering strategy involving the overexpression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 32 publications
1
47
0
Order By: Relevance
“…Furthermore, to improve the flux of the MVA pathway, we also introduced truncated HMG1 and the mutant transcription factor upc2‐1 , which has been successfully used to enhance terpenoid production in a yeast system (Bröker et al, 2018; Zhang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, to improve the flux of the MVA pathway, we also introduced truncated HMG1 and the mutant transcription factor upc2‐1 , which has been successfully used to enhance terpenoid production in a yeast system (Bröker et al, 2018; Zhang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This system allows the use of β‐estradiol to induce the expression of genes driven by GAL promoters, independent of the presence or absence of galactose or glucose. To boost triterpenoid production in yeast, the overexpression of influential enzymes in the endogenous MVA pathway, such as 3‐hydroxy‐3‐methylglutaryl‐coenzyme A reductase (HMGR) or squalene epoxidase, enhances precursor availability for heterologous triterpenoid production (Bröker, Müller, van Deenen, Prüfer, & Gronover, 2018; Dong et al, 2018; Moses et al, 2014). Overexpression of the mutant transcription factor upc2‐1 , which upregulates the transcription level of the native MVA pathway (Scalcinati et al, 2012), can increase the β‐amyrin level up to 65‐fold (Zhang, Cao, Liu, Li, & Li, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Proteins from yeast were extracted as already described in Bröker et al . (). Concentrations of either latex or yeast proteins were determined via Bradford assay (Bradford, ).…”
Section: Methodsmentioning
confidence: 97%
“…To extract triterpenes from the different latex fractions, the isolated phases were lyophilized and the protocol developed for triterpene measurement in yeast (Bröker et al ., ) was applied, but 100 μL of Betuline (2.5 mg/mL stock solution in acetone) was used as internal standard.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it has been reported that genetic manipulations on HMGR, including truncation of N-terminal domain, led to considerable accumulation of terpenes in transgenic plants and yeast (Bansal et al, 2018;Bröker et al, 2018;Lee et al, 2019). Although HMGR has been extensively characterized in model eukaryotic organisms, little is known about its features in diatoms.…”
Section: Introductionmentioning
confidence: 99%